2020
DOI: 10.1002/mds.27932
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Ventilatory Dysfunction: A Plausible Mechanism for Dyspnea in Parkinson's Disease?

Abstract: Dyspnea is an under‐recognized and debilitating symptom that is reported in up to 40% of patients with Parkinson's disease and may have multiple origins. Despite its frequency, it is poorly researched, and there is a general lack of understanding of the pathophysiology of dyspnea and respiratory dysfunction in PD. Consequently, a number of PD patients are labelled as having “unexplained dyspnea.” Studies to date have focused mainly on evaluating ventilatory capacity and lung volumes, and little is known about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 93 publications
1
11
0
Order By: Relevance
“…This suggests that decline in pulmonary function approached clinical significance. However, the earlier study [7] showed a similar decline in FEV 1 and DL CO in the observational group, suggesting that pulmonary decline is related to PD progression rather than CVT-301 inhalation [23]. The mean number of doses taken per day during the present study was about 2.…”
Section: Discussionsupporting
confidence: 45%
“…This suggests that decline in pulmonary function approached clinical significance. However, the earlier study [7] showed a similar decline in FEV 1 and DL CO in the observational group, suggesting that pulmonary decline is related to PD progression rather than CVT-301 inhalation [23]. The mean number of doses taken per day during the present study was about 2.…”
Section: Discussionsupporting
confidence: 45%
“…6 Accumulating evidence attributes important roles of oxygen availability to α-synuclein pathology initiation and progression. Ventilatory dysfunction is indeed a common but underrecognized and underinvestigated symptom in PD 7 and other α-synucleinopathies. 8 Already more than 20 years ago, Serebrovskaya and colleagues 9 reported impaired hypoxic ventilatory responses in PD-patients.…”
Section: A Possible Role Of Hypoxia In Pd Pathogenesismentioning
confidence: 99%
“…[6][7][8][9] Patients with PD are frailer than the general population because of disease-related factors and agerelated comorbidities. [2][3][4]10,11 A higher COVID-19 mortality rate has been described in advanced PD patients in association with older age and longer disease duration. 12 Our primary objective was to investigate the effects of COVID-19 on motor and nonmotor symptoms in a community-based PD cohort.…”
mentioning
confidence: 99%
“…COVID‐19 may worsen PD by a number of mechanisms, 2‐4 including pharmacodynamics changes (eg, reciprocal interactions between the dopaminergic and renin‐angiotensin systems in the substantia nigra and striatum 5 ) as well as systemic inflammatory responses 6‐9 . Patients with PD are frailer than the general population because of disease‐related factors and age‐related comorbidities 2‐4,10,11 . A higher COVID‐19 mortality rate has been described in advanced PD patients in association with older age and longer disease duration 12 …”
mentioning
confidence: 99%